Coeliac disease-associated risk variants in TNFAIP3 and REL implicate altered NF-κB signalling. Issue 8 (24th February 2009) - Trynka, G; Zhernakova, A; Romanos, J; Franke, L; Hunt, K A; Turner, G; Bruinenberg, M; Heap, G A; Platteel, M; Ryan, A W; de Kovel, C; Holmes, G K T; et al.
Abstract : Objective: Our previous coeliac disease genome-wide association study (GWAS) implicated risk variants in the human leucocyte antigen (HLA) region and eight novel risk regions. To identify more coeliac disease loci, we selected 458 single nucleotide polymorphisms (SNPs) that showed more modest association in the GWAS for genotyping and analysis in four independent cohorts. Design: 458 SNPs were assayed in 1682 cases and 3258 controls from three populations (UK, Irish and Dutch). We combined the results with the original GWAS cohort (767 UK cases and 1422 controls); six SNPs showed association with p<1×10 −04 and were then genotyped in an independent Italian coeliac cohort (538 cases and 593 controls). Results: We identified two novel coeliac disease risk regions: 6q23.3 ( OLIG3-TNFAIP3 ) and 2p16.1 ( REL ), both of which reached genome-wide significance in the combined analysis of all 2987 cases and 5273 controls (rs2327832 p = 1.3×10 −08, and rs842647 p = 5.2×10 −07 ). We investigated the expression of these genes in the RNA isolated from biopsies and from whole blood RNA. We did not observe any changes in gene expression, nor in the correlation of genotype with gene expression. Conclusions: Both TNFAIP3 (A20, at the protein level) and REL are key mediators in the nuclear factor kappa B (NF-κB) inflammatory signalling pathway. For the first time, a role for primary heritable variation in this important biological pathway predisposing to coeliac disease has been identified. Currently, the HLA risk factors and the 10 established non-HLA risk factors explain ∼40% of the heritability of coeliac disease.